Modification of perforated plate in fluidized-bed combustor to provide sufficient air supply in the combustion - Erdiwansyah, Erdiwansyah; Mahidin, Mahidin; Husin, Husni; Faisal, Muhammad; Usman, Usman; Muhtadin, Muhtadin; Gani, Asri; Rizalman, Mamat (Global Digital Central, 2022)
The modification of the perforated plate applied in this study aims to provide sufficient air access into the combustion chamber. Burning experiments were carried out with three different types of fuel (such as palm kernel shell (PKS), oil palm midrib (OPM), and empty fruit bunches (EFB). The purpose of the experiment with the modification of the perforated plate is to investigate the combustion temperature and the rate of heat transfer in the boiler. The fluidized-bed combustor (FBC) combustion chamber is used as the combustion chamber. Experimental results were obtained at four different points using a Digital Thermometer with a thermocouple. The experimental results show that the highest heat transfer rate is obtained from PKS fuel of 8.258 W/m for the M-1 measurement point. The measurement results on the M-2 highest heat transfer rate were recorded from OPM fuel of 7.392 W/m. The highest combustion temperature is obtained from OPM fuel, which is 884oC for the M-1 measurement point. The combustion temperature of the PKS combustion process is slightly higher at 896oC. However, the combustion temperature produced during the combustion of PKS shows a less good trend than OPM. Overall, the fuel used in this test can be completely burned and unsaturated by providing sufficient air supply into the combustion chamber. Modification of the perforated plate with the addition of air supply in the combustion chamber is a novelty found in this study.